A trans-dimensional approach to the behavioral aspects of depression - Bessa, João M.; Mesquita, Ana R.; Oliveira, Mário; Pêgo, José M.; Cerqueira, João J.; Palha, Joana A.; Almeida, Osborne F.; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2009)
Depression, a complex mood disorder, displays high comorbidity with anxiety and cognitive disorders. To establish the extent of inter-dependence between these behavioral domains, we here undertook a systematic analysis to establish interactions between mood (assessed with the forced-swimming [FST] and sucrose consumption tests [SCT]), anxiety (elevated-plus maze [EPM] and novelty suppressed feeding [NSF] tests) and cognition (spatial memory and behavioral flexibility tests) in rats exposed to unpredictable chronic-mild-stress (uCMS). Expectedly, uCMS induced depressive-like behavior, a hyperanxious phenotype and cognitive impairment; with the exception of the measure of anxiety in the EPM, these effects were attenuated by antidepressants (imipramine, fluoxetine). Measures of mood by the FST and SCT were strongly correlated, whereas no significant correlations were found between the different measures of anxiety (EPM and NSF); likewise, measures of cognition by spatial memory and behavioral flexibility tests were poorly correlated. Inter-domain analysis revealed significant correlations between mood (FST and SCT) and anxiety-like behavior (NSF, but not EPM). Furthermore, significant correlations were found between cognitive performance (reverse learning task) and mood (FST and SCT) and anxiety-like behavior (NSF). These results demonstrate interactions between different behavioral domains that crosscut the disciplines of psychiatry and neurology.